Perempuan Gianyar dan Belenggu Ranah Publik dan Privat - Ni Made Ras Amanda Gelgel (Jurnal Kajian Bali (Journal of Bali Studies), 2016)
Women’s roles in political and social world have been looked down by the society. The patriarchy system adhered by the Balinese people make women’s position subordinated to men. Even though women have big roles not just in private sector but also in public sector, Balinese’s women still think they do not have big contribution in their family. It is also happening in Gianyar, Bali. People in Gianyar Bali have a strict Balinese’s culture that make women have more role besides the other women in Indonesia. The research problem is what are women’s perception about their role in private and public sectors? The research was based on quantitative method by using questionnaire to 400 sample in Gianyar Bali. Research came out that women in Gianyar were spending their time dealing with household job and customary matters. They did not have time for themselves and consider themselves remain in the subordinated position. Women in Gianyar live under high hegemonic of their roles both in private and public spheres.